2022
DOI: 10.1039/d2ra03312g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity, and molecular modelling studies of potent cytotoxic podophyllotoxin-naphthoquinone compounds

Abstract: A new approach for the synthesis of podophyllotoxin-naphthoquinone compounds using microwave-assisted three-component reactions is reported in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…The synthesized C‐ZnO NPs sample displayed a less crystalline structure due to low‐temperature synthesis. [ 22 ] The regular particle phase and size discovery of materials was estimated by XRD configuration using a X'pert Pro diffractometer (Phillips, Cu‐Kα radiation, λ Cu = 1.5148 Å) operated at 30 mA and 40 kV recorded in the 2 θ with the range between 10° and 90° (scan rate 1°/min). Figure 3b, illustrates the FTIR spectra using KBr pellets: O–H stretching (3417.5 cm −1 ), C–H stretching (2850.0 cm −1 ), C=O stretching (1475.0 cm −1 ), –CH 2 stretching (1134.5 cm −1 ), aliphatic –CH stretching (1024.8 cm −1 ), ZnO (511.1 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized C‐ZnO NPs sample displayed a less crystalline structure due to low‐temperature synthesis. [ 22 ] The regular particle phase and size discovery of materials was estimated by XRD configuration using a X'pert Pro diffractometer (Phillips, Cu‐Kα radiation, λ Cu = 1.5148 Å) operated at 30 mA and 40 kV recorded in the 2 θ with the range between 10° and 90° (scan rate 1°/min). Figure 3b, illustrates the FTIR spectra using KBr pellets: O–H stretching (3417.5 cm −1 ), C–H stretching (2850.0 cm −1 ), C=O stretching (1475.0 cm −1 ), –CH 2 stretching (1134.5 cm −1 ), aliphatic –CH stretching (1024.8 cm −1 ), ZnO (511.1 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesized C-ZnO NPs sample displayed a less crystalline structure due to low-temperature synthesis. [22] The regular density and strain were analysed using subsequent expressions (equations 2-4) and the data are given in the Table 1.…”
Section: Xrd and Ftir Analysismentioning
confidence: 99%
“…44 A new class of agents with potential antitumor activity, known as podophyllotoxin-naphthoquinone derivatives (33), are derived from 2-aminonaphthalene-1,4-dione (32) in Scheme 13 in the same procedures as described. 45 In a separate study, Van Nguyen et al, showed that microwave-assisted three-component reactions can be used to synthesize podophyllotoxin-naphthoquinone compounds (33) using the stepwise thermal reaction. 46 The cytotoxicity prole of each synthetic compound was tested against four cancerous cell lines (MCF7, A549, KB, and HepG2) as well as against a noncancerous cell line, Hek-293.…”
Section: Diphenyl-1457-tetrahydrofuro[34-b]pyridinementioning
confidence: 99%
“…Shi et al, disclosed the microwave-assisted regioselective and facile synthesis of signicant 3-functionalized indole compounds (46) via a domino reaction of tetronic acid (1) with arylglyoxal (45) and anilines (15) as starting materials in a solvent system containing ethanol and water (1 : 1) in tri-uoroacetic acid (TFA) (Scheme 25). This method can be highly regarded due to its outstanding and remarkable advantages such as simplicity of practicality, short reaction time, green solvents, using non-metal, availability of raw materials, and high regioselectivity.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation